Internal security vs. external options: a goal-shielding explanation of how employability differentially shapes unethical pro-organizational behavior - Niu, Yulin; Liu, Dandan; Niu, Xiongying (Frontiers in Psychology, 2025)
IntroductionThe role of employability in employees' unethical decision-making remains unclear. Drawing on goal shielding theory, this research investigates how internal and external employability differentially influence unethical pro-organizational behavior (UPB). We propose that these relationships are mediated by bottom-line mentality (BLM) and moderated by employees' risk propensity.MethodsWe conducted two multi-wave survey studies in China. Study 1 (N = 273) provided an initial test of the direct and curvilinear relationships. Study 2 (N = 316) tested the full mediated moderation model, with data on employability and risk propensity collected at Time 1, BLM at Time 2, and UPB at Time 3.ResultsThe findings revealed distinct pathways for the two dimensions of employability. Internal employability was negatively associated with UPB, an indirect effect mediated by a reduction in BLM. This negative indirect relationship was significantly stronger for employees with low risk propensity. Conversely, we found an indirect, inverted U-shaped relationship between external employability and UPB via BLM, such that moderate external employability was associated with the highest levels of BLM and UPB. This non-linear effect was not moderated by risk propensity.DiscussionThese findings offer a new theoretical lens for understanding the motivational mechanisms behind UPB, highlighting how internal job security can reduce unethical conduct while moderate external opportunities may paradoxically increase it. The results provide practical implications for organizations on managing employee career development to prevent unethical behavior.